Aristotelian-Thomistic image of the world in terms of Piotr Lenartowicz SJ and the scientific image of the world: Meta-scientific aspects - Duchliński, Piotr (Studia Ecologiae et Bioethicae, 2019)
The aim of this article is to reconstruct the world-image outlined in the philosophical analyses by the Cracovian Jesuit philosopher and biologist Piotr Lenartowicz SJ. The reconstruction shows that he adopted an Aristotelian-Thomistic image of the world, in which the category of substance plays an overarching role, whose heuristic function reveals itself in a special way in the description and explanation of the dynamics of biological life. The article critically assesses this image by confronting it with the modern so-called ‘scientific image’ of the world, as embraced by those who support a scientific context for philosophising. This leads to a highlighting of epistemological limitations on the applicability of the Aristotelian category of substance in respect to the description of living beings. Moreover, it is shown that discussions involving supporters of different world-images (the scientific and Aristotelian-Thomistic ones) are ultimately undecidable, as the acceptance of these images involves personality-related factors such as epistemic faith and emotions. These have the effect of making those who embrace such world-images unwilling to change their view.